Beowulf cluster: an implementation and testing / Abdul Haddis Abdul Aziz - Abdul Aziz, Abdul Haddis (2003)
The use of computers within our society has developed from the very first usage in 1945when the modern computer era began, until about 1985 when computers were large and expensive. Two modern age technologies, the development of high-speed networking and the personal computer have allowed us to break-down these price barriers and construct cost effective clusters of PCs which provide comparable performance to super-computers at a fraction of the cost. As PC's and networks are in common use, this allows most commercial organizations, governments, and educational institutions access to high performance super-computers.